2016
DOI: 10.3800/pbr.11.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on life history traits of the invasive calanoid copepod <i>Arctodiaptomus dorsalis</i> (Marsh, 1907) from Lake Taal, Philippines

Abstract: Arctodiaptomus dorsalis is an invasive calanoid copepod from America, and is now found in 23 out of 32 lakes and rivers in the Philippines. Live specimens of A. dorsalis were collected from Lake Taal and cultured in the laboratory. The specimens were reared under three different temperatures (25°C, 30°C, and 35°C) with the same food and light conditions, i.e. ~10 5 cells mL −1 of Chlamydomonas reinhardtii and 12L:12D at ~60 lx, respectively. Post-embryonic development times from hatching to adult decreased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
8
2
Order By: Relevance
“…Due to various anthropogenic activities, upwellings and runoffs of nutrients from tributaries, the trophic state of freshwater habitats may be altered. As such, these environmental changes influence the timing, reproduction rate, and survival rate of these groups of aquatic animals (Varpe et al 2007, Tordesillas et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Due to various anthropogenic activities, upwellings and runoffs of nutrients from tributaries, the trophic state of freshwater habitats may be altered. As such, these environmental changes influence the timing, reproduction rate, and survival rate of these groups of aquatic animals (Varpe et al 2007, Tordesillas et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…10 species of calanoids being recorded from a single habitat in the northeast of Thailand (Sanoamuang 1999). In general, temperature raises metabolic costs in aquatic organisms (Brown et al 2004, Liu & Ban 2017 and water temperatures can always be >25°C during the year in tropical regions (Tordesillas et al 2016). Planktonic copepods in tropical regions might exhibit higher energy demand with higher metabolic costs compared to those in temperate areas (Beyrend-Dur 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of environmental factors on the life history traits of tropical freshwater copepods are still rarely and only sporadically reported. Recent studies on the tropical calanoid Arctodiaptomus dorsalis Marsh, 1907 collected from Lake Taal (Philippines) showed that this copepod can grow to be an adult within one month, with varying survival rates of 23-67% when reared with the single algal source of Chlamydomonas reinhardtii (Tordesillas et al 2016), how-ever, the highest egg production rate was obtained under a cell concentration of 2 10 5 mL −1 at 30°C (Tordesillas et al 2018). Since food selectivity in copepods is strongly influenced by both particle quality and the abundance of alternative foods (DeMott 1986, 1989, Kiørboe 2016, the widespread distribution of copepods in tropical waters might be due to their wider utilization of available food sources in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Zooplankton population growth fundamentally depends on temperature (Jiménez‐Melero et al ; Liu et al ; Tordesillas et al ) and food availability (Kiørboe et al ; Ban ; Liu et al ), because these two factors play a key role in regulating metabolism in poikilotherms (Kiørboe et al ; Brown et al ); however, many studies have demonstrated that visually oriented predation might affect a zooplankton community, and, consequently, reduce its biomass (Jeppesen et al ; Verheye et al ; Daskalov ) and body size distribution (Brooks and Dodson ; Rettig ; Hambright ). Predation pressure on large zooplankton strongly affects the zooplankton−phytoplankton biomass ratio in both oligotrophic and eutrophic lakes (Jeppesen et al , ).…”
mentioning
confidence: 99%
“…Zooplankton population growth fundamentally depends on temperature (Jiménez-Melero et al 2012;Liu et al 2014;Tordesillas et al 2016) and food availability (Kiørboe et al 1985;Ban 1994;Liu et al 2015), because these two factors play a key role in *Correspondence: ryu.k@office.usp.ac.jp Additional Supporting Information may be found in the online version of this article.…”
mentioning
confidence: 99%